Mechanisms and functional consequences of liver failure substantially differ between endotoxaemia and faecal peritonitis in rats. (12th November 2012) - Recknagel, Peter; Gonnert, Falk A.; Halilbasic, Emina; Gajda, Mieczyslaw; Jbeily, Nayla; Lupp, Amelie; Rubio, Ignacio; Claus, Ralf A.; Kortgen, Andreas; Trauner, Michael; Singer, Mervyn; Bauer, Michael
Abstract Background Many of the concepts describing molecular mechanisms of sepsis‐induced liver failure are derived from endotoxin models. However, the biological significance of such models is questionable as the complexity of clinical sepsis and associated organ failure is only partially replicated. Aims Comparison of cytokine response, leucocyte recruitment, oxidative stress and markers of hepatic organ dysfunction in rat models of endotoxaemia or peritoneal contamination and infection (PCI). Methods Endotoxemia and polymicrobial sepsis were induced in rats by intraperitoneal injection of lipopolysaccharide (LPS) or stool suspension, respectively. Results Both insults produced clinical and laboratory signs of multiple organ dysfunction, including hepatic excretory dysfunction. However, TNF alpha, oxidative stress responses and the degree of cell death were significantly higher in endotoxaemia compared to PCI (e.g. serum TNF levels (pg/ml) at 1.5 h post‐insult: sham 5 ± 1.4, LPS 1 mg/kg bw 2176.92 ± 373.78, sepsis below detection limit; P P < 0.05). Cholestasis was significantly more pronounced in polymicrobial sepsis whereas serum bilirubin in endotoxaemic animals did not differ from sham‐operated controls (plasma levels of bilirubin (μmol/L) at 15 h after the insult: sham 7.1 ± 0.6, LPS 30 mg/kg 9.1 ± 0.6, sepsis 15.2 ± 1.3). Conclusions Polymicrobial sepsis produces profound hepatocellular dysfunction in the absence of traditional cytokine‐mediated mechanisms of cellular injury. This questions the central role of cytokines and the ensuing oxidative stress as key molecular events in mediating liver dysfunction.